FUNGSI PROGRAM PENDIDIKAN NON FORMAL ; Studi Kasus di Sanggar Kegiatan Belajar (SKB) Rokan Hulu Kabupaten Rokan Hulu - Shinta Duriyanti; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Result: The Function of Life Skills Education Program Clothing Sewing Lessons as part of non formal education program held at SKB of Rokan Hulu Regency : (1)Serves as a substitute, an addition to, and complement formal education in support of lifelong education for the community. It can be seen from the educational background of students, science students about the purpose and benefits of completing education/ courses clearly, (2) Serves develop the potential of students in the mastery of knowledge and functional skills, which include: the level of success/ achievement of learning and size assessment of learning outcomes achieved by learners, the ability of teachers/ instructors so in demonstrating the skills/ expertise to learners, the ability of teachers/ instructors in closer or associate's skills and penerapannnya in the lives of young people, a positive value for self learners, families and communities, and the ability of learners to overcome their own problems, their families and surrounding communities, (3) Serves labor produces ready made and distribute best graduates to various companies/ institutions/ home industries that need, it can be seen from the work of students before, after the course, a job and a second job after the course. The Factors that affect the functioning of Life Skills Education Program Clothing Sewing Lessons as part of non formal education program in SKB of Rokan Hulu Regency : (1) The educational background of students/ residents to learn, (2)Interest, motivation and learning objectives students/ learners in the following education/ courses, (3) The allocation of time learning/ course was too short and seemed only to fill empty time so that the achievement of learning is not optimal, and (4) Facilities and infrastructure when following learning activities/ sewing courses The SKB of Rokan Hulu Regency did not complete, and the majority of students/ learners who have finished learning/ sewing class majority does not have the capital to open a sewing business. Keyword: Programe, Education, Non Formal